2021
DOI: 10.1002/pat.5247
|View full text |Cite
|
Sign up to set email alerts
|

Development of a highly efficient selective flocculant based on functionalized β‐cyclodextrin toward beneficiation of low‐quality iron ore

Abstract: The present work is focused on the development of a novel flocculant for selective flocculation of iron ore using functionalized β‐cyclodextrin (β CD). β CD has been modified by esterification reaction with methacrylic anhydride (MAh) to form β CD methacrylate (CD‐Meth). After that, a three‐dimensional polymeric network structure has been prepared by free radical polymerization of CD‐Meth with copolymeric chain of poly (acrylamide‐co‐acrylic acid) through grafting. The synthesized material has been characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The 1 H NMR spectra of β-CD, NIPAAm, AMPS, MBA, the prepolymer solution (a mixture of all of the starting materials before polymerization), and the hydrogel have been shown in Figure . The peaks corresponding to δ = 4.97 ppm and 3.25 to 3.86 ppm present in the 1 H NMR spectrum of β-CD are due to anomeric protons and other protons (ring protons and −OH protons) of β-CD, respectively . From the 1 H NMR spectrum of NIPAAm, it is observed that the peaks at δ = 1.05 and 3.88 ppm represent H b (−CH 3 protons) and H a (−CH protons) protons, respectively.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The 1 H NMR spectra of β-CD, NIPAAm, AMPS, MBA, the prepolymer solution (a mixture of all of the starting materials before polymerization), and the hydrogel have been shown in Figure . The peaks corresponding to δ = 4.97 ppm and 3.25 to 3.86 ppm present in the 1 H NMR spectrum of β-CD are due to anomeric protons and other protons (ring protons and −OH protons) of β-CD, respectively . From the 1 H NMR spectrum of NIPAAm, it is observed that the peaks at δ = 1.05 and 3.88 ppm represent H b (−CH 3 protons) and H a (−CH protons) protons, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…The peaks corresponding to δ = 4.97 ppm and 3.25 to 3.86 ppm present in the 1 H NMR spectrum of β-CD are due to anomeric protons and other protons (ring protons and −OH protons) of β-CD, respectively. 40 From the 1 H NMR spectrum of NIPAAm, it is observed that the peaks at δ = 1.05 and 3.88 ppm represent H b (−CH 3 protons) and H a (−CH protons) protons, respectively. The other existing peaks at 5.60 and 6.05 ppm are attributed to the vinylic protons of the NIPAAm molecule.…”
Section: Synthesis and Characterization Of β-Cd-cl-p-(nipaam-co-amps)mentioning
confidence: 99%